Peningkatan Hasil Belajar Materi Fikih Melalui Metode Student Teams Achievement Divisions (STAD) Dikelas 4 SDN 28 Sungai Lansek - Guspita Putri, Dewi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to determine the effect of applying the Problem-Based Learning model with the STAD method on students’ learning outcomes in the Fiqh material about welcoming the age of baligh. The research was conducted in two cycles, each including stages of planning, implementation, observation, and reflection. The results of the study show that the application of this learning model can improve students’ learning outcomes, as evidenced by the increase in average scores in Cycle II. Students were also more active in group discussions and showed greater enthusiasm in learning. However, some students were still not active in expressing their opinions. Based on these results, it can be concluded that the use of the Problem-Based Learning model with the STAD method is effective in improving students’ learning outcomes in Fiqh material